Smart surfaces : and their application in architecture and design - Klooster, Thorsten, 1966-; Boeing, Niels, 1967-; Davis, Simon; Seeger, Almut (Basel : Birkhauser, 2009)
Whether luminous wallpaper or curtains that produce electricity, innovations in surface technologies are influencing the use of materials in architecture, interior design, and design. This text brings these design fields into the creative focus of planners and designers, and emphasizes concrete possibilities for applications.
English edition of a German original.
Includes bibliographical references and index.
Keywords: Surfaces (Technology); Building materials -- Surfaces; Smart materials in architecture; Architectural design -- Technological innovations; Finishes and finishing -- Technological innovations